Implementation of Fun Model in Increasing Children's Enthusiasm in Learning at Nurul Jannah Ar-Rosikhoh Kindergarten - Azzahra, Fatimah; Alfianingrum, Fittafalla Anissavilaodra; Sulistiawati, Zahra; Rendo, Elisabeth F; Ndikeng, Yosefia S; Watini, Sri (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to describe the implementation of the Fun Model in increasing enthusiasm for learning in Group A of Nurul Jannah Ar-Rosikhoh Kindergarten. The research will be conducted in October - December 2023. This research uses descriptive research methods, description research is by means of data collection using interviews, documentation, and field notes. The observed components consist of the implementation philosophy of the Fun Model, media facilities and infrastructure in the implementation of the Fun Model, the role of teachers in the implementation of the Fun Model, the implementation policy of the Fun Model, and the evaluation of the Fun Model. The results of the study found that Nurul Jannah Ar-Rosikhoh Kindergarten had implemented the ASYIK Model learning according to the specified rules.      Kata Kunci : Model Asyik, Semangat belajar, Taman kanak-kanak Nurrul Jannah Ar-Rosikhoh